EVOLUTION OF THE CHINESE ECONOMY TO MARKET RELATIONS - R. I. Hikmatov (Russian Journal of Economics and Law, 2008)
The article is devoted to research of long and rather instructive transformation road of the Chinese economy from conditions of total and rigid state regulation to market relations by liberalization, privatization and stabilization of economic processes. Besides it in the article expresses the assumption, that the growing critical bulk of economic transformations, apparently, will come to reforming rather strong and unshakable political system of Chinese People's Republic.